The Influence of Motivation, Ability, Organizational Culture, Work Environment on Teachers Performance - et. al., Yayan Mulyana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to analyze the effect of motivation on teachers performance, the effect of ability on teachers performance, the effect of organizational culture on teachers performance and the effect of work environment on teachers performance. The method used in this research is quantitative methods, data collection methods by distributing questionnaires to teachers in Tangerang. The questionnaire was distributed electronically with simple random sampling technique and 120 respondents returned. Tools for processing data is by using PLS and using SmartPLS version 3.0 software. Based on the results of data analysis, it was concluded that motivation did not have a significant effect on teachers performance. Ability has a significant effect on teachers performance. Organizational culture has a significant effect on teachers performance. Increasing organizational learning variables increases variable teachers Performance. Work Environment has no significant effect on teachers Performance. The Contribution of this Research is to provide an understanding of the support for aspects of performance improvement in supporting and supporting the careers of educational staff